Differentiated Stem Cells Derived from Rabbit Adipose Tissue Exhibited in ‎Vitro Adipogenesis and Osteogenesis - H Al-Haideri, Dhurgham; A AL-Timmemi, Hameed (The Iraqi Journal of Veterinary Medicine, 2023)
The multipotent characteristic of rabbit adipose-derived stem cells makes them available and ‎convenient sources for isolating mesenchymal stem cells. The aim of this study was to assess ‎the differentiation in rabbit adipose-derived stem cells pre-committed to produce several ‎mesenchymal lineages in response to inductive extracellular cues to multipotent stromal cells. ‎Three grams of adipose tissue was taken from a subcutaneous region of the nape of the neck ‎and was carefully isolated to obtain mesenchymal stem cells for expanded by fourth passage. In ‎the 4th passage, active growth of mesenchymal stem cells was observed. Furthermore, the ‎research demonstrated the inherent ability of rabbit MSCs to induce differentiation in ‎osteogenic and adipogenic lineages. These mesenchymal stem cells were successfully isolated ‎from adipose tissue which differentiated into either osteocytes or adipocyte-like cells after 21 ‎and 14 days of culturing in specific osteogenic and adipogenic media, respectively. The ‎remarkable differentiation potential of rabbit mesenchymal stem cells is indicated by ‎mineralized deposition to the osteocytes and lipid droplets accumulated in the cytoplasm lipid ‎vacuoles in the adipocytes‎.